Beyond conventional corporate responses to climate change towards deep decarbonization: a systematic literature review - Matthew P. Johnson; Theresa S. Rötzel; Brigitte Frank (Management Review Quarterly, 2023)
Over the past 20 years, the literature on corporate responses to climate change has offered a vast array of theoretical and practical insights into organizational efforts to reduce business-related carbon emissions. However, it remains unclear whether these efforts will result in significant reductions of carbon emissions. Presently, it becomes crucial to understand, if, why, and how companies can effectively respond to the current challenges of deep decarbonization, defined as the process of emission reduction down to, or close to, zero to limit global warming. By means of a systematic literature review with 370 identified papers, we are able to categorize the main findings of the literature according to the four most common areas of investigation, including drivers, actions, barriers, and facilitators. Additionally, we conduct a comparative analysis of the literature along these four areas of investigation according to two categories: conventional responses and deep decarbonization responses. The results show that the literature on conventional responses to climate change (n0.167em=0.167em321) extensively covers all four areas of investigation; however, it only touches on the descriptive (i.e., 'what') aspects of decarbonization. The recent and emerging literature on deep decarbonization responses (n0.167em=0.167em49) provides novel insights on the prescriptive (i.e., 'why' and 'how') aspects of deep decarbonization. However, this literature is restricted to mostly regional and industrial foci, and it does not connect drivers, barriers, and facilitators in a systematic way. Thus, we highlight key implications for future research and practice in order to effectively address corporate deep decarbonization.
Keywords: 650; Carbon emissions; Corporate responses; Climate change; Decarbonization; Low carbon; Systematic review